A high-purity light metal-doped LiNbO3 piezoelectric coating and its preparation method
By doping light metal elements into the target of the LiNbO3 piezoelectric coating and depositing the doped lithium niobate piezoelectric coating using magnetron sputtering technology, the problems of Li deficiency and impurity phase formation are solved, and a piezoelectric coating with high purity and excellent performance are achieved.
Patent Information
- Application Number
- CN202411632487.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-15
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2044-11-15
AI Technical Summary
The low atomic weight of Li elements makes it difficult for LiNbO3 piezoelectric coating to be uniformly deposited during magnetron sputtering, and Li deficiency and impurity phase formation are prone to occur, affecting the purity and performance of the coating.
Doping light metal elements such as Cr, Sc, Zr, Cu, Zn, Fe, Ti, Ni, Al, Co, Y in the target, the doped lithium niobate piezoelectric coating is deposited through magnetron sputtering technology, and the doped elements and their content are adjusted to optimize the piezoelectric constant and ultrasonic signal of the coating.
The preparation of a high-purity LiNbO3 piezoelectric coating is achieved, avoiding the formation of lithium deficiency phase and impurity phase, and improving the piezoelectric performance and high temperature stability of the coating.
Smart Images

Figure CN119144930B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of lithium niobate piezoelectric coatings, and in particular to a method for preparing a high-purity light metal-doped LiNbO3 piezoelectric coating. Background Art
[0002] Among the ultrasonic sensors commonly used in the industrial field, lithium niobate (LiNbO3) is a common coating material for preparing piezoelectric thin films. At present, magnetron sputtering technology is generally used to prepare lithium niobate into a piezoelectric coating and coat it on the substrate. Magnetron sputtering refers to the collision of electrons with argon atoms in the process of flying toward the substrate under the action of an electric field, causing them to ionize and produce Ar positive ions and new electrons; under the action of the electric field, the new electrons fly toward the substrate, and the Ar positive ions fly toward the cathode target and bombard the target surface with high energy, causing the target material to sputter. Among the sputtered particles, neutral target atoms or molecules are deposited on the substrate to form a thin film.
[0003] However, the low atomic weight of the Li element poses a great problem for the sputtering growth of LiNbO3 piezoelectric coatings. Due to the short mean free path, some Li atoms are easily scattered in the gas mixture and diffuse to the wall of the deposition chamber of the magnetron sputtering equipment instead of being transferred to the substrate. In order to solve the above problems, the deposition of non-stoichiometric lithium niobate films has been reported in the literature. Maintaining a low substrate temperature can weaken the Li deficiency phenomenon. Combined with sputtering parameters such as gas pressure and RF power, they are conducive to reducing the formation of lithium-deficient phases (such as LiNb3O8) and lithium-rich phases (such as Li3NbO4), and improving the purity of LiNbO3 in piezoelectric coatings. Summary of the invention
[0004] The present invention provides a high-purity light metal doped LiNbO3 piezoelectric coating and a preparation method thereof. By doping certain light metal elements in the target material, the prepared lithium niobate piezoelectric coating does not contain LiNb3O8 lithium-deficient phase, nor does it contain impurity phases such as NbO and Nb2O5, and is a high-purity LiNbO3 piezoelectric coating; by adjusting the doping elements and their content, a piezoelectric constant and ultrasonic signal superior to those of pure lithium niobate coating can be obtained. The technical solution of the present invention is specifically implemented by the following technologies.
[0005] The present invention provides a method for preparing a high-purity light metal-doped LiNbO3 piezoelectric coating, comprising the following steps:
[0006] Designing a light metal element doped lithium niobate target, wherein the light metal refers to a metal located before Nb in the periodic table, and generally at least one of Cr, Sc, Zr, Cu, Zn, Fe, Ti, Ni, Al, Co, and Y can be selected;
[0007] Polishing and cleaning substrates and magnetron sputtering equipment;
[0008] When a stainless steel substrate is used, a natural oxide layer will form on the surface of the substrate, which will affect the bonding performance between the coating and the substrate, reduce the conductivity of the substrate and the bracket, and destroy the bias uniformity. Therefore, in some implementation cases, it is necessary to use 600-1500 mesh sandpaper to grind the front and back of the stainless steel substrate;
[0009] In order to fully remove the surface dirt of the magnetron sputtering equipment and improve the conductivity, in some implementation cases, a grinder and 600-1000 mesh sandpaper are used to grind the key components of the magnetron sputtering equipment, such as the substrate holder, stainless steel sheet, support seat, target fixing ring and bolts.
[0010] Installing the light metal element-doped lithium niobate target and substrate in the magnetron sputtering equipment;
[0011] The specific installation method is that the target is fixed by a fixing ring and bolts, and the substrate is suspended on the substrate bracket by a stainless steel sheet. At the same time, in order to facilitate the subsequent cleaning of the target surface without contaminating the substrate, the support seat needs to be rotated so that the front side of the substrate (i.e., the surface for depositing and coating the lithium niobate piezoelectric coating) and the surface of the light metal element doped lithium niobate target are in a non-relative state;
[0012] Start the magnetron sputtering equipment (turn on mechanical pumps, molecular pumps, heaters and other components) until the ideal vacuum degree and target temperature are reached;
[0013] Rotating the front side of the substrate to a non-opposite state with the surface of the light metal element-doped lithium niobate target, setting environmental parameters, and cleaning the surface of the light metal element-doped lithium niobate target;
[0014] The front side of the substrate is rotated to face the surface of the light metal element doped lithium niobate target material, and environmental parameters are set to deposit the light metal element doped lithium niobate piezoelectric coating on the front side of the substrate by radio frequency magnetron sputtering;
[0015] Setting the environmental parameters includes introducing Ar gas and O2 gas and controlling the inflow flow rate, setting the RF power and bias voltage.
[0016] In the preparation method of the above-mentioned high-purity light metal-doped LiNbO3 piezoelectric coating provided by the present invention, the substrate is not limited in size and material range, and an experimental substrate or an industrial substrate can be selected. Among them, the experimental substrate can be selected from a single crystal silicon wafer or a stainless steel sheet, which is used to characterize the surface morphology, cross-sectional morphology, film thickness, crystal structure, elemental composition and other information of the coating, providing a reference for industrial applications. The industrial substrate is mainly a bolt, which is used to measure ultrasonic signals and test the piezoelectric properties and high-temperature stability of the coating.
[0017] Furthermore, based on the atomic mass of the light metal, the number of doped atoms of the light metal accounts for 0.25-8.5%.
[0018] Furthermore, when the light metal is Cr, the number of doped atoms accounts for 1.1-6.42%.
[0019] Furthermore, when the light metal is Sc, the amount of doping atoms accounts for 1.4-3.0%.
[0020] Furthermore, when the light metal is Zr, the number of doped atoms accounts for 1.01-3.34%.
[0021] Furthermore, when the light metal is Cu, the number of doped atoms accounts for 0.86-6.72%.
[0022] Furthermore, when the light metal is Zn, the amount of doped atoms accounts for 1.83-3.81%.
[0023] Furthermore, when the light metal is Fe, the number of doped atoms accounts for 2.1-4.83%.
[0024] Furthermore, when the light metal is Ti, the amount of doped atoms accounts for 0.27-1.4%.
[0025] Furthermore, when the light metal is Ni, the number of doped atoms accounts for 0.55-5.11%.
[0026] Furthermore, when the light metal is Al, the amount of doping atoms accounts for 0.7-1.25%.
[0027] Furthermore, when the light metal is Co, the number of doped atoms accounts for 5.2-8.3%.
[0028] Furthermore, when the light metal is Y, the number of doping atoms accounts for 1.60-5.03%.
[0029] Furthermore, the ideal vacuum degree is (1 – 5)×10 -3 Pa.
[0030] Furthermore, the target temperature for heating the magnetron sputtering device may be selected to be 100-200°C.
[0031] Furthermore, in setting the environmental parameters, the flow volume ratio of the introduced Ar gas and O2 gas is 4 / 1-6 / 1, and the total flow rate of the Ar gas and O2 gas is 0.9-2.0 Pa.
[0032] Furthermore, in the setting of environmental parameters, the RF power is 800-900 W and the bias voltage is 2-10 V.
[0033] Furthermore, the distance between the front surface of the substrate and the surface of the light metal element-doped lithium niobate target is 4.5-7 cm.
[0034] Furthermore, the surface cleaning time of the light metal element doped lithium niobate target material is 6-12 min.
[0035] Furthermore, the deposition time of the light metal-doped LiNbO3 piezoelectric coating is 6-9 h.
[0036] In some implementation cases of the present invention, the preparation method of the light metal doped LiNbO3 target provided by the present invention is:
[0037] Add light metals to the mixed raw materials of Nb2O5 and Li2O in a molar ratio of 1:1 as needed, and mix them thoroughly in a ball mill for 5-10 hours to form a uniform raw material; sieve, weigh, and mold to make a cylindrical light metal-doped target with a diameter of 14.7-19.7 cm and a thickness of 4.1-5.1 mm;
[0038] The light metal doped target is annealed to reduce the hardness of the target, improve the uniformity of grain size and length, and facilitate obtaining a higher target sputtering rate. The specific annealing method is to first treat at 900℃ for 60 minutes and then at 1100℃ for 2 hours;
[0039] After the target material is cooled naturally, the surface and outer circle are stripped and processed, and a copper backing plate (15-20cm in diameter and 3.1-4.1mm in thickness) with a diameter slightly larger than the target material is bonded with high-temperature resistant glue, and then cleaned and dried to form the required light metal-doped lithium niobate target material.
[0040] By observing the microscopic morphology and crystal structure of lithium niobate piezoelectric coatings doped with the above-mentioned light metals, it can be seen that these coatings have excellent columnar crystal structures, do not contain lithium-deficient phase LiNb3O8, and do not contain impurity phases such as NbO and Nb2O5. They are high-purity LiNbO3 piezoelectric coatings with excellent spherical grains and columnar crystal structures.
[0041] The present invention also provides a high-purity light metal-doped LiNbO3 piezoelectric coating prepared by the above preparation method.
[0042] Compared with the prior art, the present invention is beneficial in that: the light metal doped LiNbO3 piezoelectric coating prepared by the present invention by doping several specific metals in the target material of magnetron sputtering has good spherical crystal and columnar crystal structure through observation of microscopic morphology and structure, and does not contain lithium-deficient phase LiNb3O8, nor does it contain impurity phases such as NbO and Nb2O5, and is a high-purity LiNbO3 piezoelectric coating. By adjusting the doping elements and their content, piezoelectric constants and ultrasonic signals that are superior to those of pure lithium niobate coatings can be obtained, and the prepared light metal doped LiNbO3 piezoelectric coating has excellent high-temperature performance stability. BRIEF DESCRIPTION OF THE DRAWINGS
[0043] Figure 1 This is the crystal structure of the Zr-doped lithium niobate piezoelectric coating of Experimental Example 1.
[0044] Figure 2 This is the surface morphology of the lithium niobate piezoelectric coating in Experimental Example 1 with the Zr-doped atoms accounting for 1.59%.
[0045] Figure 3 This is the crystal structure of the Zn-doped lithium niobate piezoelectric coating of Experimental Example 2.
[0046] Figure 4 This is the surface morphology of the lithium niobate piezoelectric coating in Experimental Example 2, in which the number of Zn-doped atoms accounts for 2.49%.
[0047] Figure 5 Ultrasonic signals (ultrasonic intensity, V) of the lithium niobate piezoelectric coating in which the number of Zn-doped atoms accounts for 2.49% of Experimental Example 2 and the pure lithium niobate piezoelectric coating of the comparative example.
[0048] Figure 6 Ultrasonic signal (longitudinal wave intensity, V) and piezoelectric constant (pC / N) of the Zn-doped lithium niobate piezoelectric coating of Experimental Example 2.
[0049] Figure 7 This is the crystal structure of the Ti-doped lithium niobate piezoelectric coating of Experimental Example 3.
[0050] Figure 8 The surface and cross-sectional morphologies of the lithium niobate piezoelectric coating in Experimental Example 3, in which the number of Ti-doped atoms accounts for 0.68%.
[0051] Fig. 9 Ultrasonic signals (ultrasonic intensity, V) of the lithium niobate piezoelectric coating with Ti doping amount of 0.68% in Experimental Example 3 and the pure lithium niobate piezoelectric coating in the comparative example.
[0052] Fig.10 are the ultrasonic signal (longitudinal wave intensity, V) and piezoelectric constant (pC / N) of the Ti-doped lithium niobate piezoelectric coating of Experimental Example 3, where Fig.10(a) is the data before annealing. Fig.10 (b) in the figure is the data after high temperature annealing at 700℃ for 5h.
[0053] Fig.11 This is the crystal structure of the Al-doped lithium niobate piezoelectric coating of Experimental Example 4.
[0054] Fig.12 This is the surface morphology of the lithium niobate piezoelectric coating in Experimental Example 4, in which the number of Al-doped atoms accounts for 0.99%. DETAILED DESCRIPTION
[0055] The technical solution of the present invention will be described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0056] The method for preparing the high-purity light metal-doped LiNbO3 piezoelectric coating of the present invention comprises the following steps:
[0057] (1) Design a lithium niobate target doped with a light metal, wherein the light metal is at least one of Cr, Sc, Zr, Cu, Zn, Fe, Ti, Ni, Al, Co, and Y.
[0058] (2) Cleaning substrates and magnetron sputtering equipment:
[0059] ① Substrate deoxidation treatment: For stainless steel substrates, since a natural oxide layer will form on the surface of the substrate, which affects the bonding performance between the coating and the substrate, reduces the conductivity of the substrate and the bracket, and destroys the uniformity of the bias voltage, it is necessary to use 600-1500 mesh sandpaper to polish the surface and back of the stainless steel to be coated;
[0060] ② Use a grinder and 600-1000 mesh sandpaper to grind the substrate holder, stainless steel sheet, support seat, target fixing ring and bolts to fully remove surface dirt and improve conductivity.
[0061] (3) The target material and substrate are installed in the magnetron sputtering equipment: the target material is fixed by a fixing ring and bolts, and the substrate is suspended on the substrate holder by a stainless steel sheet. At the same time, in order to facilitate the subsequent cleaning of the target material surface without contaminating the substrate, the support seat needs to be rotated to set the front side of the substrate (i.e., the surface for depositing the lithium niobate piezoelectric coating) and the surface of the target material in a non-relative state.
[0062] (3) Turn on the mechanical pump, molecular pump, heater and other magnetron sputtering equipment components, and evacuate the equipment to the ideal vacuum degree (1 – 5)×10 -3Pa, and heated to the target temperature of 100-200°C;
[0063] (4) Clean the target surface: Introduce Ar and O2, with Ar / O2 between 4 / 1-6 / 1 and a total flow rate between 0.9 Pa-2.0 Pa. Set the RF power between 800-900 W and the bias voltage between 2-10 V. Clean the target for 5-15 min.
[0064] (5) After the target material is cleaned, a light-element-doped lithium niobate piezoelectric coating is deposited by radio frequency magnetron sputtering: the substrate is rotated so that its front side is opposite to the target surface with a spacing of 4.5 cm-7 cm, and the light-element-doped lithium niobate coating is deposited. Ar and O2 are introduced, and Ar / O2 is between 4 / 1-6 / 1, and the total flow rate is between 0.9 Pa-2.0 Pa. The radio frequency power is set between 800-900 W, the bias voltage is set between 2-10 V, and the deposition time is 6-9 h.
[0065] The structure, morphology, elements, ultrasonic properties and piezoelectric properties of the above-mentioned light metal-doped lithium niobate coating were tested.
[0066] In some implementation cases, based on the atomic mass of the light metal, the amount of doped atoms of the light metal accounts for 0.25-8.5%.
[0067] Specifically, when the light metal is Cr, the number of doped atoms accounts for 1.1-6.42%.
[0068] When the light metal is Sc, the amount of doping atoms accounts for 1.4-3.0%.
[0069] When the light metal is Zr, the number of doped atoms accounts for 1.01-3.34%.
[0070] When the light metal is Cu, the number of doped atoms accounts for 0.86-6.72%.
[0071] When the light metal is Zn, the number of doped atoms accounts for 1.83-3.81%.
[0072] When the light metal is Fe, the number of doped atoms accounts for 2.1-4.83%.
[0073] When the light metal is Ti, the amount of doping atoms accounts for 0.27-1.4%.
[0074] When the light metal is Ni, the number of doped atoms accounts for 0.55-5.11%.
[0075] When the light metal is Al, the amount of doping atoms accounts for 0.7-1.25%.
[0076] When the light metal is Co, the number of doped atoms accounts for 5.2-8.3%.
[0077] When the light metal is Y, the number of doped atoms accounts for 1.60 – 5.03%.
[0078] In some embodiments of the present invention, the preparation method of the light metal doped LiNbO3 target material can be selected as follows:
[0079] (1) Adding light metals to the mixed raw materials of Nb2O5 and Li2O in a molar ratio of 1:1 as needed, and fully mixing them in a ball mill for 5-10 hours to form a uniform raw material; sieving, weighing, and molding to make a cylindrical light metal-doped target with a diameter of 14.7-19.7 cm and a thickness of 4.1-5.1 mm;
[0080] (2) Annealing treatment is performed on the light metal doped target to reduce the hardness of the target, improve the uniformity of grain size and length, and facilitate obtaining a higher sputtering rate. The specific annealing treatment method is to first treat at 900°C for 60 minutes and then at 1100°C for 2 hours;
[0081] (3) After the target material is cooled naturally, the surface and outer circle are stripped and bonded with a copper backing plate (15-20 cm in diameter and 3.1-4.1 mm in thickness) with a diameter slightly larger than the target material using high temperature resistant glue, and then cleaned and dried to form the required light metal doped lithium niobate target material.
[0082] In the following four test examples of the present invention, pure lithium niobate target (without any metal element or any other substance doped) was selected as a control to prepare pure lithium niobate piezoelectric coating. The method for preparing the target (deposition steps and equipment parameters, etc.) is basically the same as the method for preparing the target doped with light metal, the only difference being that light metal or other substances are not doped in step (1). After testing, the ultrasonic signal of the formed pure lithium niobate piezoelectric coating before annealing is 0.45V, and the piezoelectric constant d 33 is 2.6 pC / N, the ultrasonic signal is 1.2V after high temperature annealing at 700℃ for 5h, and the piezoelectric constant d 33 It is 4.6 pC / N (ultrasonic performance test parameters are: transmitting voltage 100 V, gain 40 dB).
[0083] Experimental Example 1: Effect of the proportion of Zr doping atoms on the performance of high-purity light metal doped LiNbO3 piezoelectric coating
[0084] The method for preparing the high-purity light metal-doped LiNbO3 piezoelectric coating provided in this test example comprises the following steps:
[0085] (1) Design of Zr-doped lithium niobate target.
[0086] Three lithium niobate targets were designed, all of which were composed of Nb2O5 and Li2O as basic components, and also contained ZrO, with the Zr atomic content being 1.24%, 1.59% and 2.42% respectively;
[0087] The preparation method of the target material in this test example is:
[0088] ① According to the above-mentioned Zr atomic content requirements, ZrO was added to the mixed raw materials of Nb2O5 and Li2O with a molar ratio of 1:1, and the mixture was put into a ball mill and mixed thoroughly for 6 hours. The formed uniform raw materials were sieved, weighed, and molded to make cylindrical Zr metal-doped targets with a diameter of 14.7 cm and a thickness of 4.2 mm;
[0089] ② Annealing treatment was performed at 900℃ for 60 min and 1100℃ for 2h in sequence;
[0090] ③ After the target material is cooled naturally, the flat surface and outer circle are demolded, and a copper back plate with a diameter of 15 cm and a thickness of 3.2 mm is bound with high-temperature resistant glue, cleaned and dried to form the required Zr-doped lithium niobate target material.
[0091] (2) Polishing and cleaning substrates and magnetron sputtering equipment.
[0092] ① Substrate deoxidation treatment: stainless steel substrate is selected; since a natural oxide layer will form on the surface of the substrate, which affects the bonding performance between the coating and the substrate, reduces the conductivity of the substrate and the bracket, and destroys the uniformity of the bias voltage, it is necessary to use 1200-grit sandpaper to polish the surface and back of the stainless steel to be coated;
[0093] ② Use a grinder and 800-grit sandpaper to grind key components such as the substrate holder, stainless steel sheet, support seat, target fixing ring and bolts used in the magnetron sputtering equipment in turn to fully remove surface dirt and improve conductivity.
[0094] (3) Installing the target and substrate in the magnetron sputtering device: The target is fixed by a fixing ring and bolts, and the substrate is suspended on the substrate holder by a stainless steel sheet. In order to facilitate the cleaning of the target surface without contaminating the substrate, the support seat needs to be rotated to set the front side of the substrate (i.e., the surface for depositing the lithium niobate piezoelectric coating) and the surface of the target in a non-relative state.
[0095] (4) Turn on the mechanical pump, molecular pump, and heater to create a vacuum degree of 3.2×10 -3 Pa, temperature is 150℃ environment.
[0096] (5) Cleaning the target surface: Rotate the substrate so that its back side is opposite to the target surface to clean the target surface; introduce Ar and O2, Ar / O26 / 1, with a total flow rate of 2.0 Pa, and set the RF power to 900 W and the bias voltage to 7 V. Clean the target for 10 min.
[0097] (6) Magnetron sputtering was used to deposit three lithium niobate piezoelectric coatings with different Zr doping contents: after cleaning, the substrate was rotated so that its front side was opposite to the target surface with a spacing of 5.3 cm, and the Zr-doped lithium niobate coating was deposited: Ar and O2 were introduced, Ar / O26 / 1, the total flow rate was 2.0 Pa, and the RF power was set between 900 W and the bias voltage was set between 7 V. The deposition time was 8 h, and the lithium niobate piezoelectric coating was deposited on the substrate surface.
[0098] (7) Carry out structural, morphological and elemental tests on the obtained Zr-doped lithium niobate piezoelectric coating.
[0099] The structure, morphology and element test results of Experimental Example 1 are shown in Figure 1-2 As shown, Figure 1 is the relevant crystal structure, Figure 2 The surface morphology of the lithium niobate piezoelectric coating with a Zr atomic content of 1.59%. Figure 1 and 2 It can be seen that the three lithium niobate piezoelectric coatings with different proportions of Zr-doped atoms do not contain LiNb3O8 lithium-deficient phases, nor do they contain impurity phases such as NbO and Nb2O5. They are high-purity LiNbO3 piezoelectric coatings with good spherical grains and columnar crystal structures.
[0100] Experimental Example 2: Effect of the proportion of Zn doping atoms on the performance of high-purity light metal-doped LiNbO3 piezoelectric coatings
[0101] The method for preparing the high-purity light metal-doped LiNbO3 piezoelectric coating provided in this test example comprises the following steps:
[0102] (1) Design of Zn-doped lithium niobate target:
[0103] Three lithium niobate targets were designed, all of which were composed of Nb2O5 and Li2O as basic components, and also contained ZnO, with Zn atomic contents of 2.06%, 2.49% and 3.62% respectively;
[0104] The preparation method of the target material in this test example is:
[0105] ① According to the above-mentioned Zn atomic content requirements, ZnO was added to the mixed raw materials of Nb2O5 and Li2O with a molar ratio of 1:1, and the mixture was put into a ball mill and mixed thoroughly for 6 hours. The formed uniform raw materials were sieved, weighed, and molded to make cylindrical Zn metal-doped targets with a diameter of 14.7 cm and a thickness of 4.2 mm;
[0106] ② Annealing treatment was performed at 900℃ for 60 min and 1100℃ for 2h in sequence;
[0107] ③ After the target material is cooled naturally, the surface and outer circle are demolded, and a copper back plate with a diameter of 15 cm and a thickness of 3.2 mm is bound with high-temperature resistant glue, and then cleaned and dried to form the required Zn-doped lithium niobate target material.
[0108] (2) Polishing and cleaning substrates and magnetron sputtering equipment.
[0109] ① Substrate deoxidation treatment: stainless steel substrate is selected; since a natural oxide layer will form on the surface of the substrate, which affects the bonding performance between the coating and the substrate, reduces the conductivity of the substrate and the bracket, and destroys the uniformity of the bias voltage, it is necessary to use 1200-grit sandpaper to polish the surface and back of the stainless steel to be coated;
[0110] ② Use a grinder and 800-grit sandpaper to grind the key components of the magnetron sputtering equipment, such as the sample holder, stainless steel sheet, support seat, target fixing ring and bolts, to fully remove surface dirt and improve conductivity.
[0111] (3) Installing the target and substrate in the magnetron sputtering device: The target is fixed by a fixing ring and bolts, and the substrate is suspended on the substrate holder by a stainless steel sheet. In order to facilitate the cleaning of the target surface without contaminating the substrate, the support seat needs to be rotated to set the front side of the substrate (i.e., the surface for depositing the lithium niobate piezoelectric coating) and the surface of the target in a non-relative state.
[0112] (4) Turn on the mechanical pump, molecular pump, and heater to create a vacuum degree of 3.2×10 -3 Pa, temperature is 150℃ environment.
[0113] (5) Cleaning the target surface: Rotate the substrate so that its back side is opposite to the target surface to clean the target surface; introduce Ar and O2, Ar / O26 / 1, with a total flow rate of 2.0 Pa, and set the RF power to 900 W and the bias voltage to 7 V. Clean the target for 10 min.
[0114] (6) Magnetron sputtering was used to deposit three lithium niobate piezoelectric coatings with different Zn doping contents: after cleaning, the substrate was rotated so that its front side was opposite to the target surface with a distance of 5.3 cm, and the Zn-doped lithium niobate coating was deposited: Ar and O2 were introduced, Ar / O26 / 1, the total flow rate was 2.0 Pa, and the RF power was set between 900 W and the bias voltage was set between 7 V. The deposition time was 8 h, and the lithium niobate piezoelectric coating was deposited on the substrate surface.
[0115] (7) The obtained Zn-doped lithium niobate piezoelectric coating was tested for structure, morphology, elements, ultrasonic properties (ultrasonic performance test parameters were emission voltage 100 V, gain 40 dB) and piezoelectric properties.
[0116] The structure, morphology and element test results of Experimental Example 2 are shown in Figure 3 and 4 As shown, Figure 3 is the relevant crystal structure, Figure 4 The surface morphology of the lithium niobate piezoelectric coating with a Zn atomic content of 2.49%. Figure 3 and 4 It can be seen that the three lithium niobate piezoelectric coatings with different proportions of Zn-doped atoms do not contain LiNb3O8 lithium-deficient phases, nor do they contain impurity phases such as NbO and Nb2O5. They are high-purity LiNbO3 piezoelectric coatings with excellent spherical grains and columnar crystal structures.
[0117] The ultrasonic performance and piezoelectric performance test results of Experimental Example 2 are as follows: Figure 5 and 6 As shown in the figure, the piezoelectric constants d of lithium niobate piezoelectric coatings with Zn atomic contents of 2.06%, 2.49% and 3.62% were measured. 33 They are 3.75 pC / N, 3.90 pC / N and 3.05 pC / N respectively. It can be seen that the ultrasonic signals and piezoelectric constants of the three Zn-doped lithium niobate piezoelectric coatings with different doping atomic content are stronger than those of the pure lithium niobate piezoelectric coating, and the Zn-doped lithium niobate piezoelectric coating with a Zn atomic content of 2.49% has the strongest ultrasonic signal and piezoelectric constant.
[0118] Experimental Example 3: Effect of the proportion of Ti doping atoms on the performance of high-purity LiNbO3 piezoelectric coating
[0119] The method for preparing the high-purity LiNbO3 piezoelectric coating provided in this test example comprises the following steps:
[0120] (1) Design of Ti-doped lithium niobate target:
[0121] Three lithium niobate targets were designed, all of which were composed of Nb2O5 and Li2O as basic components, and also contained TiO2, with Ti atomic contents of 0.41%, 0.68% and 1.40% respectively;
[0122] The preparation method of the target material in this test example is:
[0123] ① According to the above-mentioned Ti atomic content requirements, TiO2 was added to the mixed raw materials of Nb2O5 and Li2O with a molar ratio of 1:1, and the mixture was put into a ball mill and mixed for 6 h. The resulting uniform raw materials were sieved, weighed, and molded to produce a cylindrical Ti metal-doped target with a diameter of 14.7 cm and a thickness of 4.2 mm;
[0124] ② Annealing treatment was performed at 900℃ for 60 min and 1100℃ for 2h in sequence;
[0125] ③ After the target material is cooled naturally, the flat surface and outer circle are stripped and bonded with a copper back plate with a diameter of 15 cm and a thickness of 3.2 mm using high temperature resistant glue. The target material is cleaned and dried to form the required Ti-doped lithium niobate target material.
[0126] (2) Polish and clean the substrate and magnetron sputtering equipment. Magnetron sputtering was used to deposit three lithium niobate piezoelectric coatings with different Zn doping contents:
[0127] ① Substrate deoxidation treatment: stainless steel substrate is selected; since a natural oxide layer will form on the surface of the substrate, which affects the bonding performance between the coating and the substrate, reduces the conductivity of the substrate and the bracket, and destroys the uniformity of the bias voltage, it is necessary to use 1200-grit sandpaper to polish the surface and back of the stainless steel to be coated;
[0128] ② Use a grinder and 800-grit sandpaper to grind the key components of the magnetron sputtering equipment, such as the sample holder, stainless steel sheet, support seat, target fixing ring and bolts, to fully remove surface dirt and improve conductivity.
[0129] (3) Installing the target and substrate in the magnetron sputtering device: The target is fixed by a fixing ring and bolts, and the substrate is suspended on the substrate holder by a stainless steel sheet. In order to facilitate the cleaning of the target surface without contaminating the substrate, the support seat needs to be rotated to set the front side of the substrate (i.e., the surface for depositing the lithium niobate piezoelectric coating) and the surface of the target in a non-relative state.
[0130] (4) Turn on the mechanical pump, molecular pump, and heater to create a vacuum degree of 3.2×10 -3 Pa, environment with temperature of 150℃;
[0131] (5) Cleaning the target surface: Rotate the substrate so that its back side is opposite to the target surface to clean the target surface; introduce Ar and O2, Ar / O26 / 1, with a total flow rate of 2.0 Pa, and set the RF power to 900 W and the bias voltage to 7 V. Clean the target for 10 min.
[0132] (6) Magnetron sputtering was used to deposit three lithium niobate piezoelectric coatings with different Ti doping contents: after cleaning, the substrate was rotated so that its front side was opposite to the target surface with a distance of 5.3 cm, and Ti-doped lithium niobate coating was deposited: Ar and O2 were introduced, Ar / O26 / 1, the total flow rate was 2.0 Pa, and the RF power was set between 900 W and the bias voltage was set between 7 V. The deposition time was 8 h, and the lithium niobate piezoelectric coating was deposited on the substrate surface.
[0133] (7) The obtained Ti-doped lithium niobate piezoelectric coating was subjected to structural, morphological, elemental, ultrasonic performance (ultrasonic performance test parameters are: emission voltage 100 V, gain 40 dB), and piezoelectric performance tests.
[0134] (8) The obtained Ti-doped lithium niobate piezoelectric coating was subjected to a high-temperature annealing experiment at 700°C for 5 h, and then the acoustic performance (ultrasonic performance test parameters are: emission voltage 100 V, gain 40 dB) and piezoelectric performance tests were carried out to verify the performance stability.
[0135] The structure, morphology and element test results of Experimental Example 3 are as follows: Figure 7 and 8 As shown, Figure 7 is the relevant crystal structure, Figure 8 The surface morphology of lithium niobate piezoelectric coating with a Ti atomic content of 0.68%. Figure 7 and 8 It can be seen that the three lithium niobate piezoelectric coatings with different proportions of Ti doped atoms do not contain LiNb3O8 lithium-deficient phase, nor do they contain impurity phases such as NbO and Nb2O5. They are high-purity LiNbO3 piezoelectric coatings with good spherical grains and columnar crystal structures.
[0136] The ultrasonic performance and piezoelectric performance test results of Experimental Example 3 before annealing are as follows: Fig. 9 and Fig.10 As shown in (a), the piezoelectric constants d of lithium niobate piezoelectric coatings with Ti atomic contents of 0.41%, 0.68% and 1.40% were measured. 33 They are 3.55 pC / N, 4.45 pC / N and 3.15 pC / N respectively. It can be seen that the ultrasonic signals and piezoelectric constants of the three Ti-doped lithium niobate piezoelectric coatings with different doping atomic content are stronger than those of the pure lithium niobate piezoelectric coating, and the Ti-doped lithium niobate piezoelectric coating with a Ti atomic content of 0.68% has the strongest ultrasonic signal and piezoelectric constant.
[0137] The ultrasonic and piezoelectric properties test results of Experimental Example 3 after annealing at 700°C for 5h are as follows: Fig.10 As shown in (b), the piezoelectric constants d of lithium niobate piezoelectric coatings with Ti atomic contents of 0.41%, 0.68% and 1.40% are 33 , ultrasonic signals are still stronger than those of pure lithium niobate piezoelectric coatings, and the Ti-doped lithium niobate piezoelectric coating with a Ti atomic content of 0.68% has the strongest ultrasonic signal and piezoelectric constant. At the same time, compared with the data before annealing, the piezoelectric constant d of the Ti-doped lithium niobate piezoelectric coating after high-temperature annealing at 700℃ for 5h is 33 , and ultrasonic signals are greatly improved, indicating that the Ti-doped lithium niobate piezoelectric coating has excellent high-temperature performance stability.
[0138] Example 4: Effect of the ratio of Al doping atoms on the performance of high-purity light metal doped LiNbO3 piezoelectric coating
[0139] The method for preparing the high-purity light metal-doped LiNbO3 piezoelectric coating provided in this test example comprises the following steps:
[0140] (1) Design of Al-doped lithium niobate target:
[0141] Three lithium niobate targets were designed, all of which were composed of Nb2O5 and Li2O as basic components, and also contained Al2O3, with Al atomic contents of 0.73%, 0.99% and 1.25% respectively;
[0142] The preparation method of the target material in this test example is:
[0143] ① According to the above Al atomic content requirements, Al2O3 was added to the mixed raw materials of Nb2O5 and Li2O with a molar ratio of 1:1, and the mixture was put into a ball mill and mixed thoroughly for 6 hours. The formed uniform raw materials were sieved, weighed, and molded to make cylindrical Al metal-doped targets with a diameter of 14.7 cm and a thickness of 4.2 mm;
[0144] ② Annealing treatment was performed at 900℃ for 60 min and 1100℃ for 2h in sequence;
[0145] ③ After the target material is cooled naturally, the surface and outer circle are demolded, and a copper back plate with a diameter of 15 cm and a thickness of 3.2 mm is bound with high-temperature resistant glue, and then cleaned and dried to form the required Al-doped lithium niobate target material.
[0146] (2) Polishing and cleaning substrates and magnetron sputtering equipment.
[0147] ① Substrate deoxidation treatment: stainless steel substrate is selected; since a natural oxide layer will form on the surface of the substrate, which affects the bonding performance between the coating and the substrate, reduces the conductivity of the substrate and the bracket, and destroys the uniformity of the bias voltage, it is necessary to use 1200-grit sandpaper to polish the surface and back of the stainless steel to be coated;
[0148] ② Use a grinder and 800-grit sandpaper to grind the key components of the magnetron sputtering equipment, such as the sample holder, stainless steel sheet, support seat, target fixing ring and bolts, to fully remove surface dirt and improve conductivity.
[0149] (3) Installing the target and substrate in the magnetron sputtering device: The target is fixed by a fixing ring and bolts, and the substrate is suspended on the substrate holder by a stainless steel sheet. In order to facilitate the cleaning of the target surface without contaminating the substrate, the support seat needs to be rotated to set the front side of the substrate (i.e., the surface for depositing the lithium niobate piezoelectric coating) and the surface of the target in a non-relative state.
[0150] (4) Turn on the mechanical pump, molecular pump, and heater to create a vacuum degree of 3.2×10 -3 Pa, temperature is 150℃ environment.
[0151] (5) Cleaning the target surface: Rotate the substrate so that its back side is opposite to the target surface to clean the target surface; introduce Ar and O2, Ar / O26 / 1, with a total flow rate of 2.0 Pa, and set the RF power to 900 W and the bias voltage to 7 V. Clean the target for 10 min.
[0152] (6) Magnetron sputtering was used to deposit three lithium niobate piezoelectric coatings with different Al doping contents: after cleaning, the substrate was rotated so that its front side was opposite to the target surface with a spacing of 5.3 cm, and Al-doped lithium niobate coating was deposited: Ar and O2 were introduced, Ar / O26 / 1, the total flow rate was 2.0 Pa, and the RF power was set between 900 W and the bias voltage was set between 7 V. The deposition time was 8 h, and the lithium niobate piezoelectric coating was deposited on the substrate surface.
[0153] (7) Carry out structural, morphological and elemental tests on the obtained Al-doped lithium niobate piezoelectric coating.
[0154] The test results of Example 4 are as follows Fig.11 and 12 As shown, Fig.11 is the relevant crystal structure, Fig.12 The surface morphology of the lithium niobate piezoelectric coating with an Al atomic content of 0.99%. Fig.11 and 12It can be seen that the three lithium niobate piezoelectric coatings with different proportions of Al-doped atoms do not contain LiNb3O8 lithium-deficient phases, nor do they contain impurity phases such as NbO and Nb2O5. They are high-purity LiNbO3 piezoelectric coatings with good spherical grains and columnar crystal structures.
[0155] The above specific embodiments describe the implementation of the present invention in detail, but the present invention is not limited to the specific details in the above embodiments. Within the scope of the claims and technical concept of the present invention, the technical solution of the present invention can be modified and changed in many simple ways, and these simple modifications all belong to the protection scope of the present invention.
Claims
1. Application of high-purity light metal-doped LiNbO3 material in piezoelectric coating, characterized in that: The method for preparing the high-purity light metal-doped LiNbO3 material comprises the following steps: Design light metal element doped lithium niobate target; polish and clean substrate and magnetron sputtering equipment; Installing the light metal element-doped lithium niobate target and substrate in the magnetron sputtering equipment; Start the magnetron sputtering equipment until the ideal vacuum degree and target temperature are reached; Rotating the front side of the substrate to a non-opposite state with the surface of the light metal element-doped lithium niobate target, setting environmental parameters, and cleaning the surface of the light metal element-doped lithium niobate target; The front side of the substrate is rotated to face the surface of the light metal element doped lithium niobate target material, and environmental parameters are set to deposit the light metal element doped lithium niobate piezoelectric coating on the front side of the substrate by radio frequency magnetron sputtering; In the light metal element doped lithium niobate target, the light metal is at least one of Cr, Sc, Zr, Cu, Zn, Fe, Ti, Ni, Al, Co, and Y; Setting environmental parameters includes introducing Ar gas and O2 gas and controlling the flow rate, setting RF power and bias voltage; When the light metal is Cr, the proportion of doping atoms is 1.1-6.42%; When the light metal is Sc, the amount of doping atoms accounts for 1.4-3.0%; When the light metal is Zr, the proportion of doping atoms is 1.01-3.34%; When the light metal is Cu, the proportion of doping atoms is 0.86-6.72%; When the light metal is Zn, the proportion of doping atoms is 1.83-3.81%; When the light metal is Fe, the proportion of doping atoms is 2.1-4.83%; When the light metal is Ti, the amount of doping atoms accounts for 0.27-1.4%; When the light metal is Ni, the proportion of doping atoms is 0.55-5.11%; When the light metal is Al, the proportion of doping atoms is 0.7-1.25%; When the light metal is Co, the proportion of doping atoms is 5.2-8.3%; When the light metal is Y, the number of doped atoms accounts for 1.60 – 5.03%.
2. The use of the high-purity light metal-doped LiNbO3 material in a piezoelectric coating according to claim 1, characterized in that: The ideal vacuum degree is (1 – 5)×10 -3 Pa.
3. The use of the high-purity light metal-doped LiNbO3 material in a piezoelectric coating according to claim 1, characterized in that: The target temperature for heating the magnetron sputtering device is 100-200°C.
4. The use of the high-purity light metal-doped LiNbO3 material in a piezoelectric coating according to claim 1, characterized in that: In setting the environmental parameters, the flow volume ratio of the introduced Ar gas and O2 gas is 4 / 1-6 / 1, and the total flow rate of Ar gas and O2 gas is 0.9-2.0 Pa.
5. The use of the high-purity light metal-doped LiNbO3 material in piezoelectric coating according to claim 1, characterized in that: In the environmental parameter settings, the RF power is 800-900 W and the bias voltage is 2-10 V.
6. The use of the high-purity light metal-doped LiNbO3 material in a piezoelectric coating according to claim 1, characterized in that: The distance between the front side of the substrate and the surface of the light metal element doped lithium niobate target is 4.5-7 cm.
7. The use of the high-purity light metal-doped LiNbO3 material in a piezoelectric coating according to claim 1, characterized in that: The deposition time of light metal doped LiNbO3 piezoelectric coating is 6-9 h.